Godtfredsen syndrome – recurrent clival chondrosarcoma with 6years follow up: a case report and literature review - Lik, Thai Lim; Yong, Sze Wei; Yong, Yuin Chong; Noraini, Mohd Dusa; Yin, Peng Lai (BioMed Central, 2022)
Background: We report a rare case of Godtfredsen syndrome caused by clival chondrosarcoma and perform a review of literatures. This article also explains the clinico-anatomical correlation of this rare neurological syndrome. Case presentation: A 22-year-old gentleman presented with binocular diplopia. Clinical examination revealed an isolated right abducent nerve and right hypoglossal nerve palsy, with other cranial nerves intact. Neuroimaging revealed a right clival mass. Supraorbital craniotomy and tumour debulking were done in the same year. Histopathological examination showed low-grade chondrosarcoma. After 5-years of default, he came back with the tumour enlarged. He underwent a right orbitozygomatic craniotomy and tumour excision with 33 cycles of radiotherapy. Despite two surgeries and radiotherapy, the abducent nerve and hypoglossal nerve did not improve throughout 6 years of follow-up. Cranial nerve VI palsy is not always a false localizing sign, in Godtfredsen syndrome it serves as a localizing sign. Conclusion: To the best of our knowledge, this is the frst case report of Godtfredsen Syndrome secondary to clival chondrosarcoma. Cranial nerve VI and XII palsy with no involvement of other cranial nerves, most likely the pathology is located at the clivus